Irritable Bowel Syndrome: Gut Microbiota Dysbiosis and Psychological Co-morbidities - Bijita Bhowmick; Sharmistha Banerjee; Sanchaita Gayen; Supriya Samanta; Nilotpal Banerjee (Journal of Clinical and Diagnostic Research)
Irritable Bowel Syndrome (IBS) is a prevalent Gastrointestinal (GI) disorder, affecting approximately 10-15% of the global population, with significant implications for public health. It is characterised by chronic abdominal discomfort, altered bowel habits and a spectrum of symptoms that often co-exist with psychological conditions such as anxiety and depression. Emerging evidence highlights a critical imbalance in gut microbiota among individuals with IBS, underscoring the intricate gut-brain-microbiome axis. This dysbiosis not only exacerbates GI symptoms but also contributes to mental health challenges, creating a vicious cycle that impacts overall wellbeing. The broader consequences of IBS extend beyond individual health, leading to considerable impairment in daily functioning, reduced workplace efficiency and diminished Quality of Life (QoL). The socio-economic burden is reflected in increased rates of absenteeism, presenteeism and healthcare costs. Current therapeutic interventions, including probiotics, prebiotics, Faecal Microbiota Transplantation (FMT) and targeted medications, hold promise but require further research to establish their long-term efficacy and safety. This review aims to provide a comprehensive analysis of IBS, focusing on its microbial aetiology, the interplay with psychological co-morbidities, and its profound effects on work-related activities and societal productivity. By consolidating existing evidence, it seeks to emphasise the urgent need for innovative and effective therapeutic strategies. Addressing IBS as a multifaceted public health challenge requires interdisciplinary efforts to develop tailored interventions that alleviate its wide-ranging impacts on individuals and communities.